Effect of Cardiogenic Shock Hospital Volume on Mortality in Patients With Cardiogenic Shock - Shaefi, Shahzad (J Am Heart Assoc, 2015)
BACKGROUND: Cardiogenic shock (CS) is associated with significant morbidity, and mortality rates approach 40% to 60%. Treatment for CS requires an aggressive, sophisticated, complex, goal‐oriented, therapeutic regimen focused on early revascularization and adjunctive supportive therapies, suggesting that hospitals with greater CS volume may provide better care. The association between CS hospital volume and inpatient mortality for CS is unclear. METHODS AND RESULTS: We used the Nationwide Inpatient Sample to examine 533 179 weighted patient discharges from 2675 hospitals with CS from 2004 to 2011 and divided them into quartiles of mean annual hospital CS case volume. The primary outcome was in‐hospital mortality. Multivariate adjustments were performed to account for severity of illness, relevant comorbidities, hospital characteristics, and differences in treatment. Compared with the highest volume quartile, the adjusted odds ratio for inpatient mortality for persons admitted to hospitals in the lowest‐volume quartile (≤27 weighted cases per year) was 1.27 (95% CI 1.15 to 1.40), whereas for admission to hospitals in the low‐volume and medium‐volume quartiles, the odds ratios were 1.20 (95% CI 1.08 to 1.32) and 1.12 (95% CI 1.01 to 1.24), respectively. Similarly, improved survival was observed across quartiles, with an adjusted inpatient mortality incidence of 41.97% (95% CI 40.87 to 43.08) for hospitals with the lowest volume of CS cases and a drop to 37.01% (95% CI 35.11 to 38.96) for hospitals with the highest volume of CS cases. Analysis of treatments offered between hospital quartiles revealed that the centers with volumes in the highest quartile demonstrated significantly higher numbers of patients undergoing coronary artery bypass grafting, percutaneous coronary intervention, or intra‐aortic balloon pump counterpulsation. A similar relationship was demonstrated with the use of mechanical circulatory support (ventricular assist devices and extracorporeal membrane oxygenation), for which there was significantly higher use in the higher volume quartiles. CONCLUSIONS: We demonstrated an association between lower CS case volume and higher mortality. There is more frequent use of both standard supportive and revascularization techniques at the higher volume centers. Future directions may include examining whether early stabilization and transfer improve outcomes of patients with CS who are admitted to lower volume centers.